Associação do papaya meleira virus e de um segundo vírus de ssRNA à meleira do mamoeiro - Antunes, Tathiana Ferreira Sá (2017)
Papaya sticky disease, or “meleira”, is one of the major diseases of papaya in Brazil and Mexico, capable of causing complete crop loss. The causal agent of sticky disease was identified as an isometric virus with a double stranded RNA (dsRNA) genome, named papaya meleira virus (PMeV). In the present study, the nearly complete sequence was obtained for PMeV dsRNA which 8,814 nucleotides long and contains two putative ORFs; the predicted ORF1 and ORF2 display similarity to capsid proteins and RdRp's, respectively, from mycoviruses tentatively classified in the family Totiviridae. Besides PMeV dsRNA, a second RNA band of approximately 4.5 kb was isolated from latex of papaya plants with severe symptoms of sticky disease. The sequence obtained for the second RNA is 4,515 nucleotides long and contains two putative ORFs. The predicted ORFs 1 and 2 display 48% and 73% sequence identity, respectively, with the corresponding proteins of papaya virus Q, an umbravirus recently described infecting papaya in Ecuador. Viral purification in a sucrose gradient allowed separation of particles containing each RNA. Mass spectrometry analysis indicated that both PMeV and the second RNA (named papaya meleira virus 2, PMeV2) were encapsidated in particles formed by the protein encoded by PMeV ORF1. The presence of both PMeV and PMeV2 was confirmed in field plants showing typical symptoms of sticky disease. Interestingly, PMeV was detected alone in asymptomatic plants. Together, our results indicate that sticky disease is associated with double infection by PMeV and PMeV2.